The Role of Sharia Compliance, Governance, and Firm Size in Determining Free Cash Flow: Evidence from Energy Sector - Paleva, Muhammad Irvan; Hardiono, Ryan Yusuf (IAIN Kudus, 2025)
Cash flow efficiency is essential for corporate sustainability, especially in capital-intensive industries like the energy sector. This study aims to examine the effect of sharia compliance, audit quality, government effectiveness, and firm size on free cash flow. The research employs a panel data regression approach with a random effect model, analyzing 61 energy companies listed on the Indonesia Stock Exchange from 2020 to 2023, resulting in 243 firm-year observations. The findings reveal that Sharia compliance, audit quality, and firm size have a significant positive effect on free cash flow, while government effectiveness has a significant negative effect. The study is grounded in agency theory and stakeholder theory, contributing to the Islamic corporate finance literature and financial sustainability. One limitation of this study is its sectoral focus and the exclusion of macroeconomic variables. The findings offer practical support for regulators, investors, and policymakers to enhance ethical governance and financial outcomes.